Meningkatkan Peran Serta Masyarakat dalam Mencegah Penyebaran Virus Covid-19 - Dwi Haryoto; Hari Wisodo; Sujito; Arif Hidayat; Hestiningtyas Yuli Pratiwi (Jurnal Pemberdayaan Masyarakat, 2021)
Community service has been carried out in RW 12 Kel. Merjosari Malang to increase the potential and participation of the community in health environment. The increase in the number of Covid-19 patients in Malang Raya, about 3,378 people, presents that the Covid-19 virus has increased drastically both number of patients confirmed positive and patients who died. The problems faced by partners are not understanding the Covid-19 disease, weak resources, limited funds, and difficulty accessing information. The method is socialization by conducting discussions, optimizing citizen resources, monitoring and evaluation. The result is conducting discussions, developing resources, providing training, providing counseling and assistance. Citizen involvement is to provide a place to install spraying equipment, maintain spraying facilities, provide a place to conduct training, provide human resources ready to be trained voluntarily. Citizens' anxiety and restlessness were slightly reduced by increased community understanding. Citizens give a positive assessment of service. This is proven by the percentage of residents giving a positive rating on average 95.68%, consisting of 95.33% giving a positive response, and 4.67% giving a negative response.